Investigation of a novel multigeneration system driven by a SOFC for electricity and fresh water production. (15th September 2019) - Chitgar, Nazanin; Emadi, Mohammad Ali; Chitsaz, Ata; Rosen, Marc A.
Highlights: A novel system driven by SOFC is proposed for power and fresh water production. Kalina and thermoelectric generator are integrated to recover SOFC waste heat. Effects of key parameters on the system performance are examined. The system is optimized with respect to exergy efficiency and total cost rate. The system is capable of producing 225 m 3 /day fresh water and 1.3 MW power. Abstract: An integrated system for the simultaneous production of electricity and fresh water is proposed based on a solid oxide fuel cell (SOFC). In this system, a Kalina cycle is utilized to recover waste heat from the SOFC stack. Furthermore, a thermoelectric generator is employed to recover the heat dissipated in the Kalina condenser. In the proposed configuration, the energy required for reverse osmosis desalination can be supplied by a Kalina cycle and a thermoelectric generator. The system uses methane as its primary fuel. Electrochemical equations for the fuel cell are considered, as are thermodynamic and exergy-economic relations for the components of the system. The effects on the performance of the proposed hybrid system of variations in design parameters such as current density, SOFC inlet temperature, fuel utilization factor, inlet pressure of the Kalina cycle turbine and concentration of water-ammonia solution in the Kalina cycle are examined. The SOFC stack is seen to make the highest contribution to the total exergy destruction of the system. To strive simultaneously for maximum efficiency and minimum total cost, optimization is carried out using a genetic algorithm. The total optimum point of the system is the trade-off between the optimization objectives. At this point, the net electrical power production is about 1.3 MW and the production rate of fresh water reaches 226 m 3 /day, while the exergy efficiency and total cost rate are 54% and 36.8 $/hr, respectively.